Automated Reasoning with Analytic Tableaux and Related Methods 18th International Conference, TABLEAUX 2009, Oslo, Norway, July 6-10, 2009, Proceedings - Giese, Martin; Waaler, Arild (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the refereed proceedings of the 18th International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2009, held in Oslo, Norway, in July 2009. The 21 revised research papers presented together with 1 system description and 2 invited talks were carefully reviewed and selected from 44 submissions. The papers cover many topics in the wide range of applications of tableaux and related methods in areas such as hardware and software verfications, semantic technologies, and knowledge engineering.